Soil Crust Formation Influenced by the Impact of Sprinkler Irrigation Systems in Iraq - Ghazal, Kariem A. (International Journal of Psychosocial Rehabilitation, 2020)
Field experiment was conducted to assess the impact of sprinkler irrigation system on the surface soil crusting in the silty clay texture. Three sprinkler models were used difference in nozzle size and geometric shape.Sprinklers have been utilized to irrigate cultivated and uncultivated plots in order to determine the contribution of vegetative cover which can reduce the impact of sprinkler droplets.The size distribution of the sprinkler droplets for each model was determined at different distances from the sprinkler center. Various physical soil properties were tested and statistically analyzed to understand the contribution of sprinkler irrigation in soil crusting formation. The parameters included soil infiltration, bulk density, mean weight diameter, porosity, and micromorphological study of the thin section of soil crust. The results indicated that the impact of sprinkler irrigation did not exceed two centimeters of soil depth. The outcomes included increasing the bulk density of the soil, decreasing the infiltration rate, reducing the porosity and the mean weight diameter of the soil crust. The vegetative cover caused to aggravate the sprinkler irrigation impact compared to the uncultivated plots.